Carved Komari (Vulva) Stones from Rapa Nui: Museum Objects, Legacy Data and Contemporary Local History - Kaeppler, Adrienne L.; Van Tilburg, Jo Anne (Waka Kuaka, 2020)
The authors examine selected stone objects in the J.L. Young Collection, Bernice P. Bishop Museum, Honolulu. Two were named by Young “Maea Momoa” (ma‘ea momoa; lit. ‘stone for chickens’). One of the ma‘ea momoa is a “pillow stone” (ŋarua) or basaltic beach cobble incised with komari (vulva motifs). The other is a “Bar of stone” lavishly embellished with similar motifs. Six other objects are said to be “fetish stones”. A possible ‘Orongo provenance for the incised “Bar of stone” is raised and tested, and toponymic and linguistic data are offered in support of a new interpretation of the origin of the hakatoro repe ‘elongation of the clitoris’ ritual and the function of one incised “fetish stone” in that process. This research calls attention to the traditional role of women in ‘Orongo ceremonies and employs relatively obscure museum collection objects and their previously overlooked documentation, thus uniting multiple data strands to reveal new details of Rapanui ritual life.